А) х=12; у=17
Б) х=-7; у=-10
С) у=12; х=11
Д) х=2 ; у= 13
Е) x=3/2; y=-1/2
Пошаговое объяснение:
А) 2*(х-5)=у-3
х+5=у
2(х-5)=х+5-3; 12+5=у
х=12
у=17
ответ : х=12; у=17
Б) 3*(х – у) = 9
2*х = у – 4
3(x-y)=9
y=4+2x
3(x-(4+2x))=9; y=4+2(-7)
x=-7
y=-10
ответ: х=-7; у=-10
С) 3*(у – 6) – 2*(4 – х ) = 12
4Х + 2у + 4 = 11
3(y-6)-8+6x=12
y=7/2-2x
3(7/2-2x-6) - 2(4-x)=12
x=-55/8
y=7/2-2(-55/8)
y=69/4
ответ: у=12; х=11
Д) х + у – 10 = 5
у – х = 11
x+y=15
-x+y=11
2y=26 ; -x+13=11
y=13
x=2
ответ: х=2 ; у= 13
Е) 3х – 5 = у
Х + 2 = у
3x-y=5
x-y=2
2x=3
ответ : x=3/2; y=-1/2
7√3sinx-1+2sin²x-10-1=0
sinx=a
2a²+7√3a-12=0
D=147+96=243
a1=(-7√3-9√3)/4=-4√3⇒sinx=-4√3<-1 нет решения
a2=(-7√3+9√3)/4=√3/2⇒sinx=√3/2
x=π/3+2πk U x=2π/3+2πk
3π/2≤π/3+2πk≤3π U 3π/2≤2π/3+2πk≤3π
9≤2+12k≤18 U 9≤4+12k≤18
7≤12k≤16 U 5≤12k≤14
7/12≤k≤16/12 U 5/12≤k≤14/12
k=1⇒x=π/3+2π=7π/3 U x=2π/3+2π=8π/3
проверка
x=7π/3
log(8)(7√3*sin7π/3-cos14π/3-10)=log(8)(7√3*√3/2-(-1/2)-10)=
=log(8)(10,5+0,5-10)=log(8)1=0
0=0
x=8π/3
log(8)(7√3sin8π/3-cos16π/3-10)=log(8)(7√3*√3/2-(-1/2)-10)=
=log(8)(10,5+0,5-10)=log(8)1=0
0=0